DOI: 10.11606/d.11.2012.tde-14032012-084521
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação da reflectometria no domínio do tempo (TDR) na estimativa da condutividade elétrica da solução do solo e de concentrações de nitrato, potássio e cloreto em coluna de solo não saturado

Abstract: Aplicação da reflectometria no domínio do tempo (TDR) na estimativa da condutividade elétrica da solução do solo e de concentrações de nitrato, potássio e cloreto em coluna de solo não saturado / Isaac de Matos Ponciano. --versão revisada de acordo com a resolução CoPGr 5890 de 2010. --Piracicaba, 2012. 113 p. : il. Dissertação (Mestrado) --Escola Superior de Agricultura "Luiz de Queiroz", 2012. 1. Condutividade elétrica do solo 2. Cloreto 3. Fertirrigação -Manejo 4. Íons 5. Modelos matemáticos 6. Monitorament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
(65 reference statements)
1
1
0
2
Order By: Relevance
“…These results are corroborated by those of Ponciano (2012), who observed that in CEw's estimate the model of Vogeler et al (1996) adjusts better to soils with clay texture characteristics both by the application of KCl and by the application of KNO3 via irrigation water, and in sandy soil the models from Vogeler et al (1996) and Munõz-Carpena et al (2005) presented a similar quality of adjustments being classified as "Very good". For both soils, there was a positive correlation (r+) for the estimation of nitrate and potassium concentration in the soil solution from water content data (θ) and apparent electrical conductivity (CEa) when a linear or power type relation is introduced to the adapted models (Vogeler et al, 1996;Munõz-Carpena et al, 2005).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…These results are corroborated by those of Ponciano (2012), who observed that in CEw's estimate the model of Vogeler et al (1996) adjusts better to soils with clay texture characteristics both by the application of KCl and by the application of KNO3 via irrigation water, and in sandy soil the models from Vogeler et al (1996) and Munõz-Carpena et al (2005) presented a similar quality of adjustments being classified as "Very good". For both soils, there was a positive correlation (r+) for the estimation of nitrate and potassium concentration in the soil solution from water content data (θ) and apparent electrical conductivity (CEa) when a linear or power type relation is introduced to the adapted models (Vogeler et al, 1996;Munõz-Carpena et al, 2005).…”
Section: Resultssupporting
confidence: 68%
“…In addition to these statistical indicators, Pearson's correlation coefficient (r) (Figueiredo Filho and Silva Júnior, 2009) and the "c" index (according to the methodology presented by Ponciano, 2012) were also used to indicate the performance of the model.…”
Section: Methodsmentioning
confidence: 99%
“…A evaporação, ou escoamento (processos dinâmicos), durante os trabalhos de amostragem podem também alterar os valores de umidade (CONCIANI et al, 1996).…”
Section: Métodos De Monitoramento Da Umidade Do Solounclassified
“…A água tem constante dielétrica 80, o ar 1 e o solo seco o valor da constante dielétrica varia entre 2,5 e 7. Assim, pequenas variações de umidade podem ser observadas pela variação da constante dielétrica (CONCIANI et al, 1996). SOUZA et al (1999) realizou um estudo onde verificou a possibilidade de utilização de sondas multihaste com diferentes segmentações, em um equipamento de TDR -Trase System I.…”
Section: Métodos De Monitoramento Da Umidade Do Solounclassified